DAMPAK PANDEMI COVID-19 TERHADAP KEGIATAN PEMBELAJARAN ONLINE DI STMIK KOMPUTAMA MAJENANG - Setiawan, Willy; Yusuf, Dede (Jurnal Teknologi dan Bisnis, 2020)
COVID-19 is a virus originating from Wuhan, China that spread rapidly throughout the world. Indonesia began to be infected since the beginning of March 2020. The impact of the spread of COVID-19 caused losses to many countries, especially in the economic field. In the field of education, learning activities carried out in class are replaced online as a result of the spread of COVID-19 starting from elementary school to tertiary level. This study uses descriptive qualitative methods that describe online learning activities at STMIK Komputama Majenang during the COVID-19 pandemic that was held at home online. The object consists of 5 students of STMIK Komputama Majenang. Data collection was carried out using a questionnaire containing questions related to online learning at STMIK Komputama Majenang during the COVID-19 pandemic. Based on the results of research, online learning activities at STMIK Komputama Majenang have been effective and run well. Some applications used in online learning are Web E-learning, WhatsApp, Telegram, Edmodo, YouTube, Zoom, and Google Classroom. Constraints experienced during online learning are problems with a bad internet connection, limited quota, difficulty in learning, and the presence of other people's distractions when learning takes place.